The Effect of Cultural Literacy, Ethnocentrism and Xenophobia on Intercultural Sensitivity in Intern Nurses in Türkiye - Gümüş Şekerci, Yasemin; Yıldırım, Beyza Gül (UI Scholars Hub, 2025)
Background: With rising migration and multicultural patient populations, understanding the factors that shape intercultural sensitivity among healthcare workers has become essential. This study aims to determine the effect of cultural literacy, ethnocentrism, and xenophobia on intercultural sensitivity in nurse interns. Methods: This cross-sectional study was conducted with 206 intern nurses from three universities in a province of Türkiye. A simple random sampling method is used. Data are collected by using the Introductory Information Form, Intercultural Sensitivity Scale, Cultural Literacy Scale, Ethnocentrism Scale, and Xenophobia Scale. Multiple regression is used for data analysis. Results: Cultural literacy (β = 0.327, p < 0.001) was found to be a positive predictor of intercultural sensitivity, while ethnocentrism (β = −0.194, p < 0.001) and xenophobia (β = −0.210, p < 0.001) were found to be negative predictors of intercultural sensitivity. Cultural literacy, ethnocentrism, and xenophobia explained 44.3% of the variation in intercultural sensitivity (Adjusted R2 = 0.443). Conclusion: The study found that cultural literacy plays a positive role in increasing intercultural sensitivity, while ethnocentrism and xenophobia negatively affect this sensitivity.